The effect of vitamin E on lipid peroxidation and some antioxidants in blood and milk of cows with subclinical mastitis - Şimşek, Halil; Aksakal, Mesut (Ankara Üniversitesi, 2005)
This study was carried out to determine the effects of vitamin E on lipid peroxidation and some antioxidant substances in subclinical mastitic dairy cows. Forty cows were assigned to two groups by California Mastitis Test (CMT) and somatic cell count (SCC). 2.000 IU vitamin E was injected to cows of mastitic group by intramuscular route every other day for twenty days. Blood and milk samples from cows in healthy, mastitic and treatment groups were taken; milk SCC was counted vitamin E, Se and MDA concentrations in milk and plasma, erytrocyte GSH, GSH-Px and Catalase activities and leucocyte GSH-Px and MDA levels were determined. Differences in milk SCC, vitamin E and MDA, plasma vitamin E, Se and MDA; leucocyte GSH-Px; erytrocyte GSH, GSH-Px and Catalase levels between healthy and mastitic groups were significantly changed while differences in milk Se and leucocyte MDA levels were not significant. Mastitic and treatment groups in milk SCC and MDA, plasma vitamin E and MDA; leucocyte GSH-Px; erythrocyte GSH and GSH-Px levels were found as significant stastistically whereas differences in milk vitamin E and Se levels; plasma Se; leucocyte MDA and erythrocyte Catalase activities were not stastistically significant. Differences in milk SCC and MDA, plasma Se and MDA; erytrocyte GSH and GSH-Px; leucocyte GSH-Px levels between healthy and treatment groups were significantly changed while differences in milk vitamin E and Se, plasma vitamin E, erythrocyte Catalase activities and leucocyte MDA levels were not significant

Bu araştırmada, subklinik mastitisli ineklerde E vitamininin lipit peroksidasyon ve bazı antioksidan düzeylerine etkisi araştırıldı. Araştırmada, 40 adet inek kullanıldı. Sağlıklı ve mastitisli inekler, Kaliforniya Mastitis Testi (CMT) ve somatik hücre sayısına (SHS) göre belirlendi. Mastitisli ineklere 20 gün boyunca gün aşırı 2.000 IU E vitamini kas içi uygulandı. Sağlıklı, mastitisli ve tedavi gruplarındaki ineklerden alınan kan ve süt örneklerinde süt SHS, süt ve plazma E vitamini, Se ve MDA, eritrosit GSH, GSH-Px ve Katalaz, lökosit GSH-Px ve MDA değerlerine bakıldı. Sağlıklı ve mastitisli grup süt SHS, E vitamini ve MDA, plazma E vitamini, Se ve MDA, lökosit GSH-Px, eritrosit GSH, GSH-Px ve Katalaz düzeyleri arasındaki fark istatistiksel olarak önemli bulundu. Süt Se ve lökosit MDA ortalamaları ise önemsiz bulundu. Mastitisli ve tedavi grupları arasında süt SHS ve MDA, plazma E vitamini ve MDA, lökosit GSH-Px, eritrosit GSH ve GSH-Px düzeyleri arasındaki fark istatistiksel olarak önemli bulundu. Süt E vitamini ve Se, plazma Se, lökosit MDA ve eritrosit Katalaz ortalamaları farkının ise istatistiksel yönden önemsiz olduğu saptandı. Sağlıklı ve tedavi grupları arasında süt SHS ve MDA, plazma Se ve MDA, eritrosit GSH ve GSH-Px, lökosit GSH-Px, düzeyleri arasındaki fark istatistiksel olarak önemli bulundu. Süt E vitamini ve Se, plazma E vitamini, eritrosit Katalaz, lökosit MDA ortalamaları farkının ise istatistiksel yönden önemsiz olduğu saptandı
Subklinik mastitisli ineklerde kan ve sütte lipit peroksidasyon ve bazı antioksidanlar üzerine E vitamininin etkisi
Keywords: Veterinary Surgery; Veteriner Cerrahi